Manhaj Al-Tafsir Al-Maudhu’i Lil Qur’an Al-Karim Dirasah Naqdiyyah Karya Samir ‘Abdurrahman Syauqi - Rohman, Moch Abdul (Ali Muchasan, 2018)
One method of interpretation of the Qur'an that is developing at this time is a method that emphasizes the theme, commonly called the method of interpretation of maudhu'i (manhaj tafsir al-maudhu'i) or topical method. In the event of an alienation of interpretations monopolized by fundamentalists with their analytical methods (tahlili) or harfiyah (literal), the method of interpretation of maudhu'i as a new manhaj can interact with the text-al-Qur'an (the Qur'an), expected to be able to help Muslims to clarify the theory in the Koran (nadhariah al-Qur'an), the purpose of the Qur'an (maqhasid al-Qur'an), and the rules of the Qur'an at the time of many thought models. The hope is that the method of interpretation of maudhu'i can be a tool (sabilan) and a knife of analysis to reveal the secrets of the Qur'an and its wisdom, which are sometimes vague in the heart, such as in the case of i'jaz al-Qur'an, conformity , tarkib skills, or the contents of thought (al-fikri) and philosophy contained in the Qur'an. Slowly, the method of referencing the maudhu'i gradually underwent a significant development, so that it was expected to provide new benefits and hopes in the course of the development